Training and Telling Experience How to Make Eco-Friendly and Healthy Soap at Pondok Pesantren Hirzu Millati Singocandi Kudus - Arina Hafadhotul Husna; Rohmatun Nafi’ah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STIKES Cendekia Utama Kudus, 2022)
The increasing number of Covid-19 cases that are getting out of control, especially in the Kudus area, Central Java, has forced the community to play a role in efforts to reduce the number of Covid-19 transmissions. Washing hands with soap is one of the steps that can break the chain of transmission of the Covid-19 virus, however, the wastewater produced by SLS which contained in soap has increased significantly due to the increasing use of soap which damage the environment. This community service activity aims to provide soft skill training on how to make eco-friendly and healthy soap and English training on